(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
Depression and nightmares are caused by Montelukast. Montelukast is a selective leukotriene receptor antagonist (LRTA) and US-FDA issued a black box warning in 2020. In this case report, a 14 year old female was prescribed a combination of Tab. Montelukast and Tab. Fexofenadine for the treatment of bronchial asthma exacerbations. After this, she started experiencing multiple episodes of depression and nightmares. The patient was asked to avoid Montelukast after which the patient’s condition improved and she was started on MDI Formoterol fumarate and Budesonide powder for inhalation and Tab. Desloratadine for further management. After stopping the drug, her condition improved. This case underlines the importance of monitoring for rare but serious side effects of leukotriene receptor antagonist and highlights the need for further research into their mechanisms and risk factors.